Student Participation in Madrasah Diniyah Awaliyah as a Predictor of Qur'anic Reading and Writing Learning Motivation - Ayu Lestari; Arlinda; Nabila Deswina Fendri; Anisa Zahara Jambak; Khoiriah (Islamic Studies and Education Journal, 2026)
Learning motivation is a crucial determinant of successful Qur'anic Reading and Writing (BTQ) instruction in non-formal Islamic educational institutions. Madrasah Diniyah Awaliyah (MDA) serves not only as a medium for improving students' Qur'anic literacy but also as an institution that fosters religious character and strengthens students' motivation to learn. This study aimed to examine the effect of students' participation in Madrasah Diniyah Awaliyah (MDA) activities on their motivation to learn Qur'anic Reading and Writing (BTQ) at Darul Ishlah Mosque, Pasir Kandang. A quantitative approach with a correlational research design was employed. The study population consisted of 60 active students, from which 20 respondents were selected through simple random sampling. Data were collected using questionnaires, observations, and documentation and analyzed through descriptive statistics, normality and linearity tests, Pearson Product-Moment correlation, and simple linear regression using IBM SPSS Statistics version 27. The findings revealed a positive and statistically significant relationship between students' participation in MDA activities and their motivation to learn BTQ, with a correlation coefficient of 0.720 (p < 0.05). The regression analysis produced a coefficient of determination (R²) of 0.518, indicating that participation in MDA activities explained 51.8% of the variance in students' learning motivation. These findings suggest that structured MDA programs, supported by continuous religious practices and positive pedagogical interactions, play an important role in strengthening students' motivation to learn the Qur'an. The study contributes to the development of non-formal Islamic education by highlighting the importance of improving teacher competence, implementing innovative instructional strategies, and strengthening collaboration among teachers, parents, and educational institutions.